Dendritic Hematite Nanoarray Photoanode Modified with a Conformal Titanium Dioxide Interlayer for Effective Charge Collection. (23rd August 2017) - Luo, Zhibin; Wang, Tuo; Zhang, Jijie; Li, Chengcheng; Li, Huimin; Gong, Jinlong
Abstract: This paper describes the introduction of a thin titanium dioxide interlayer that serves as passivation layer and dopant source for hematite (α‐Fe2 O3 ) nanoarray photoanodes. This interlayer is demonstrated to boost the photocurrent by suppressing the substrate/hematite interfacial charge recombination, and to increase the electrical conductivity by enabling Ti 4+ incorporation. The dendritic nanostructure of this photoanode with an increased solid–liquid junction area further improves the surface charge collection efficiency, generating a photocurrent of about 2.5 mA cm −2 at 1.23 V versus the reversible hydrogen electrode (vs. RHE) under air mass 1.5G illumination. A photocurrent of approximately 3.1 mA cm −2 at 1.23 V vs. RHE could be achieved by addition of an iron oxide hydroxide cocatalyst.